Technology Dissemination of Blood type Checking and Health Examination by the Thematic Community Service Program (KKN) of Alma Ata University in Hamlet of Kejambon Kidul - Nurjani A. Hasan; Rizal Fauzi; Nurzaleha Nurzaleha; Yesi Lestari; Fatma Siti Fatimah; Ratih Devi Alfiana; Fatimatasari Fatimatasari; Linda Yulyani; Mia Aulia; Mustaghfirotul Lailiyah; Nenden Azasra; Ika Muslimawati; Handayani Handayani; Amalia Zulfat (Peneliti Teknologi Teknik Indonesia, 2021)
Health examination is an examination that focuses more on primary and secondary prevention efforts, namely detecting various health factors as a whole that can cause certain diseases in the future. Health screening is important because it can help prevent degenerative diseases. Students in the community are required to be actively involved in developing community knowledge, one of which is in the health sector. Through the Community Service Program (KKN), students carry out blood type checks and free health checks for the community in the Kejambon Kidul hamlet. The method of implementing the activities is carried out with a direct approach which is divided into two stages, namely the preparation stage and the implementation stage. The results of the activity showed that the activity was attended by 68 people, consisting of 15 men and 53 women, with the distribution of blood type A; Rh+ as many as 18 people, B; Rh+ as many as 16 people, AB; Rh+ as many as 10 people, O; Rh+ as many as 22 people and 1 person with blood type O; Rh-. The results of the blood pressure examination showed that as many as 13 people had abnormal blood pressure, 12 people with hypertension and 1 person with hypotension.